Composition of Organic Carbon-Based Compounds in the Stem Wood of Quercus mongolica Seedlings Grown Under Elevated CO2 and/or O3 Concentrations - Ugawa, Shin; Hashimoto, Shoji; Hashida, Koh; Tobita, Hiroyuki; Kitao, Mitsutoshi (Frontiers in Forests and Global Change, 2021)
In this study, we examined the composition of organic constituents of stem woody tissue together with tree growth in Quercus mongolica var. grosseserrata Blume seedlings raised under controlled CO2 and/or O3 concentrations in a Free-Air Concentration Enrichment system. After exposure to ambient air (control), elevated CO2 concentration (550 μmol mol–1 CO2), elevated O3 concentration (double that of the control), and a combination of elevated CO2 and O3 concentrations during a growing season, we measured the diameter and length of stem, and biomass of sampled seedlings and quantified the lignin, extractive, and holocellulose contents of the woody tissue of current-year stems. We confirmed that the growth of seedlings was enhanced under an elevated CO2 concentration condition. In line with this, the extractive content was lower in woody tissue formed under an elevated CO2 concentration than that formed under ambient air, whereas holocellulose content showed an inverse pattern. Elevated O3 concentration itself did not change the organic constituents of the woody tissue, but it reduced the influence of an elevated CO2 concentration. We thus assume that Q. mongolica formed woody tissue with a low extractive content under the high CO2 concentration condition, although this response was possibly mitigated by an elevated O3 concentration. Extractives contains antimicrobial components such as tannins, flavonoids, quinones, and terpenoids. The decrease in extractives within the widely distributed Q. mongolica in East Asia may have a non-negligible impact on C cycling in the future earth with high atmospheric CO2 concentration.